ENERGY CONSUMPTION REDUCTION TECHNOLOGIES EQUIPMENT FOR DRYING VEGETABLE RAW MATERIALS - Цвіркун, Людмил; Омельченко, Олександр; Цвіркун, Сергій; Перекрест, Володимир; Гончаренко, Володимир (SWorldJournal, 2025)
The article states that for the food industry, drying is one of the most energy-intensive operations, as it consumes almost 50% of energy. Saving energy consumed during drying is no less important than the quality of the final product. Reducing specific e